2008
DOI: 10.1111/j.1467-9280.2008.02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Feedback to Infants' Babbling Facilitates Rapid Phonological Learning

Abstract: Infants' prelinguistic vocalizations are rarely considered relevant for communicative development. As a result, there are few studies of mechanisms underlying developmental changes in prelinguistic vocal production. Here we report the first evidence that caregivers' speech to babbling infants provides crucial, real-time guidance to the development of prelinguistic vocalizations. Mothers of 9.5-month-old infants were instructed to provide models of vocal production timed to be either contingent or noncontingent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
496
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(524 citation statements)
references
References 27 publications
20
496
1
7
Order By: Relevance
“…Behavioral evidence, however, from both adults (e.g. Okita et al, 2007;Laidlaw et al, 2011) and children (Kuhl et al, 2003;Goldstein and Schwade, 2008;Kirschner and Tomasello, 2009) suggests that live, interactive context significantly alters response to otherwise matched social stimuli. Adult neuroimaging research has begun to identify the neural bases of social interaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral evidence, however, from both adults (e.g. Okita et al, 2007;Laidlaw et al, 2011) and children (Kuhl et al, 2003;Goldstein and Schwade, 2008;Kirschner and Tomasello, 2009) suggests that live, interactive context significantly alters response to otherwise matched social stimuli. Adult neuroimaging research has begun to identify the neural bases of social interaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Under this view, infants' speech production is shaped by caregiver responses, as demonstrated by work showing that infants who receive contingent feedback to their babbles restructure them to include phonological patterns from their caregivers' speech, whereas infants who receive noncontingent feedback do not (Goldstein & Schwade, 2008). In ASD, there are three possible ways that the social feedback loop might be disordered.…”
Section: Discussionmentioning
confidence: 99%
“…Ramsdell-Hudock (2014) suggested that such behaviour may be important for receiving feedback from the caregiver when the infant is engaged in her own vocal production. Infants aged 9.5 months produce more speech-like vocalizations when the parent responds contingently to their babbling (Goldstein & Schwade, 2008). Similarly, 10-month-olds that more frequently switch their att ention between the actor and the object that is being described in a foreign language show bett er non-native phoneme discrimination at the neural level in a mismatch response paradigm (Conboy, Brooks, Meltzoff , & Kuhl, 2015).…”
Section: Social-pragmatic Cues In Articulating Facesmentioning
confidence: 99%